PROBLEMS ON INTERNATIONAL STUDENTS’ PARAGRAPHS: A CASE STUDY AT UIN MAULANA MALIK IBRAHIM MALANG - Mohamad Zubad Nurul Yaqin (Abjadia, 2021)
Ideas within student’s scientific works must meet scientific conditions, one of which is written in a good and correct paragraph. Ironically, international students at UIN Maulana Malik Ibrahim Malang still make some mistakes upon writing papers even though they have been equipped with Indonesian language competence since the first semester. The current study aims to identify the problems on international students’ paragraphs, to find their factors, and to spot alternative solutions. It employed a qualitative approach with a text analysis or discourse analysis. The data were the in the form of linguistic practices within students’ papers. They were collected, classified, and analyzed according to the research focus. Three kinds of issues were found in the papers of international students at UIN Maliki Malang: not meeting the elements of cohesion and coherence, incomplete paragraph development, and unsequential paragraph development. Each form of the error supported one another